Researcher race : social constructions in the research process - Mizock, Lauren; Harkins, Debra A. (Emerald Publishing Limited : Information Age Publishing, 2011)
Researcher Race: Social Constructions in the Research Process is designed to expose the role of researcher race in social science research. This book highlights the interaction of researcher and participant race in shaping data that is collected. Researcher Race makes the researcher's position visible via interview excerpts from a qualitative study in order to deconstruct researcher race effects in research. The book includes passages from a qualitative research study with a sample of 20 Black-identified and 20 White-identified participants, as well as a Black researcher and a White researcher. Selections of data from across different researcher-participant racial dyads illustrate how issues of researcher race can arise in research settings.Researcher Race presents the history of racial bias and maltreatment in research. A review of cultural competency theory as it pertains to research is discussed. An overview of narrative research methodology that is used in this study is also provided. Chapters focused on the research data include an exploration of participants' preferences for researcher race; the significance of off-script researcher comments during an interview; and the narratives of traumatic racism among Black and White participants. In the concluding chapter, the book expands conversations about researcher race to consider intersecting aspects of identity in researcher-participant interactions, as well as directions for future research and training.This book can serve as a guide for researchers, as well as students of research, culture, and diversity. Researcher Race: Social Constructions in the Research Process is a valuable tool for researchers interested in expanding awareness of race, oppression, and methodology.
Keywords: Racism in psychology.; Racism in the social sciences.; Racism in medicine.; Psychology -- Research -- Moral and ethical aspects.; Social sciences -- Research -- Moral and ethical aspects.; Medicine -- Research -- Moral and ethical aspects.; Social Science -- Research.; Racism and racial discrimination, Anti-racism.; Social research and statistics.; elektronické knihy; electronic books